Ectopic ACTH syndrome. - Isidori, A; Kaltsas, G; Grossman, AB (2006)
Ectopic adrenocorticotropin secretion (EAS) accounts for 10-15% of cases of Cushing's syndrome and comprises a spectrum of tumours from undetectable isolated lesions to widespread metastatic and aggressive malignancies. EAS is often associated with severe hypercortisolaemia causing hypokalaemia, diabetes, generalized infections, hypertension and psychotic reactions. Surgical resection of the primary lesion, achievable with a curative intent in about 40% of patients with EAS, is associated with complete remission in up to 80% of such cases. It is therefore mandatory to localize the source of ectopic ACTH hypersecretion in order to stage the disease and adopt optimal treatment modalities. Modern cross-sectional imaging techniques can identify the majority of the ACTH secreting lesions, either initially or at follow-up reassessment. However, in approximately 10-20% of patients with EAS, the source of ACTH hypersecretion remains occult in spite of extensive investigation and prolonged followup. In such cases, control of the hypercortisolemia can be achieved with long-term adrenolytic medication. When conditions require a prompt and definitive resolution of the hypercortisolaemia (i.e. as in pregnancy), bilateral adrenalectomy remains an alternative option. This review focuses on the clinical features, diagnostic pitfalls, management and long-term followup of the EAS based on the extensive experience of major referral centres.